2014
DOI: 10.1002/sca.21141
|View full text |Cite
|
Sign up to set email alerts
|

X‐linked hypophosphatemic rickets: Enamel abnormalities and oral clinical findings

Abstract: X-linked hypophosphatemia (XLH) is a genetic disorder related to alterations in bones and teeth formation, due to low levels of phosphate in blood. Oral findings in XLH have been enamel and dentine abnormalities, high pulp horns, large pulp chambers, and some cases of periapical abscesses related to teeth without caries or traumatic injuries. The aim of our study was to assess the presence of enamel alterations, such as microclefts and/or structure defects in patients with XLH and give guidelines of prevention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…[ 2 ] Additionally, enamel defects, periodontal disease, and malocclusion occur in XLH. [ 5 ] Previously, it was reported that patients with VDDR-I exhibit hypoplastic enamels, large pulp chambers, short roots, and chronic periodontal disease. [ 1 , 14 ] However, there is still a lack of morphologic and histologic evidence regarding VDDR-I.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Additionally, enamel defects, periodontal disease, and malocclusion occur in XLH. [ 5 ] Previously, it was reported that patients with VDDR-I exhibit hypoplastic enamels, large pulp chambers, short roots, and chronic periodontal disease. [ 1 , 14 ] However, there is still a lack of morphologic and histologic evidence regarding VDDR-I.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D-dependent rickets type I (VDDR-I) is a rare type of rickets caused by mutation of the CYP27B1 gene, which leads to 1-α-hydroxylase enzyme deficiency and conversion disorder of 25-OH vitamin D to 1,25-(OH) 2 vitamin D. [ 1 ] Laboratory findings include hypocalcemia, hypophosphatemia, elevated serum parathyroid hormone (PTH), low serum 1,25-(OH) 2 vitamin D, and normal or increased 25(OH) vitamin D. [ 2 ] Clinical manifestations of VDDR-I display the typical characteristics of rickets, including bowleg, growth retardation and ectodermal dysplasia. [ 3 ] Although dental abnormalities have been reported in many types of rickets such as vitamin D-dependent rickets type II (VDDR- II), [ 4 ] X-linked hypophosphatemia (XLH) [ 5 ] and vitamin D–resistant rickets (VDRR), [ 6 ] the dental manifestation of VDDR-I and its long-term dental intervention remain largely unclear. Considering that dental abnormalities in children affect chewing ability, pronunciation, facial appearance, and mental health, it is important to provide information on diseases with dental problems for pediatricians and dentists to effectively manage these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Some clinical studies reported the absence of enamel alterations in subjects affected by XLH [11]. However, Cremonesi et al, have shown by scanning electron microscopy, an irregular structured, slightly hypoplastic enamel in XLH teeth when compared to the images of control group [12]. In both deciduous and permanent teeth, pulp chambers could be enlarged, resembling taurodontism and prominent pulp horns extend up to the dentino-enamel junction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Dental findings of this condition are enlarged pulp chambers, pulp horns which spread outside the dentino-enamel junction, enamel and dentine defects, poorly defined lamina-dura, short roots and hypoplastic alveolar ridge (4,(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of all these factors contribute to recurrent dental abscesses in VDRR cases. Bacteria and their toxins which come from the oral cavity to the pulp cause pulpitis, pulp necrosis, periapical recurrent abscess or periapical complications without dental caries (1,2,4,5,7,(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%